(untitled) (American Journal of Islam and Society, 2012)
In August or September 1219 at the height of the Fifth Crusade, Francis of Assisi audaciously set out to meet Sultan Malik al-Kâmil of Egypt. In Saint Francis and the Sultan: The Curious History of a Christian–Muslim Encounter, historian John Tolan has produced a fascinating volume on this rather strange episode, an encounter that has captivated writers and painters for centuries. In an age when religion has lost much of its traditional power, however, the author wonders how much we can really know about the experience of Francis and al-Kâmil meeting each other “in a tent in an armed camp on the banks of the Nile, during a truce in the midst of a bloody war” (p. 4). Instead of trying to locate the real Francis and al-Kâmil in the fragments of history, Tolan asks why this particular has fascinated so many different artists. He answers, quite simply, that “for them, it was not merely a curiosity, or a footnote to the history of a crusade which failed on the banks of the Nile. It was much more: an emblematic encounter or confrontation between East and West” (p. 326). Whether it was seen as an encounter or a confrontation, in turn, depended in part on the historical, religious, and political context within which the given artist was working. In this sense, the book reads more like a metahistory of how, why, and to what effect a particular historical episode has been depicted over the years. Given the focus on such a momentous encounter between East and West, Islam and Christianity, Muslim and Christian, as well as how it has been portrayed and understood, this book should be of particular interest to students of Christian–Muslim relations and dialogue. It should also be of interest to people interested in the construction of East/West and Muslim/Christian identity ...